Vegetation record around a cement factory and the impact of dust pollution on crop productivity - Chapagain, Narahari; Dhakal, Min Raj (Nepalese Journal of Biosciences, 2013)
Effect of cement dust pollution on crop productivity in the environment of Himal Cement Factory, Kathmandu, Nepal has been studied. The productivity of the crops like wheat, maize and mustard were significantly low in the fields 1.5 km around the factory site in comparison to the fields at 3-4-km distance. Productivity of rice was least affected. Polluted area around the cement factory becomes unsuitable for vegetable production due to deposition of dust particles on the leaves. A list of plants growing around the factory has also been presented. DOI: http://dx.doi.org/10.3126/njbs.v1i0.7472 Nepalese Journal of Biosciences 1: 55-62 (2011)